Penciptaan Visual Branding Karjo (Kaose Wong Pordjo) Purworejo - Kadek Primayudi (Institut Seni Indonesia Yogyakarta, 2022)
Abstract. Karjo T-shirt merchandise has an appeal as a medium in promoting Purworejo through the visual themes of t-shirt designs that are presented. This creation is an offer for Karjo who is building brand awareness as a souvenir of Purworejo. Karjo tried to invite the people of Purworejo to be proud of the uniqueness of the city.Karjo's visual branding took advantage of the homecoming moment and gave memories to the travelers when there was a chance for a reunion, in the form of painting t-shirts for children and families under the name of the Karjo Makaryo event.This creation method uses design thinking method that begins with exploring the Karjo problem, then empathizes through social media Suwarto to the Karjo brand and conducts interviews. Based on observations, the ideas that will be processed into visual identity of Karjo Makaryo's activities will emerge and apply them to the publication media as a prototype of Karjo's branding which is expected to be carried out routinely.Relevance to Visual Communication Design Practice: Karjo Makaryo's visual identity became the beginning of a communication strategy as part of brand activation.